The Economic and Social Life in the West Tripoli and Barca during the Fatimid Era: A Historical Study (297 - 443H) / Ramdan M Ramdan Alahmar - Ramdan M , Ramdan Alahmar (2019)
The provinces of Tripoli of-the-West and Barca geographically link between the East and the West, and at the same time between the Central of Africa and the countries located on the other side of the Mediterranean Sea. The Fatimids realized the importance of the strategic location of the two provinces for their expansion project in the region. Therefore, they controlled them as early as the establishment of their Caliphate in the Islamic Maghreb in 297 H / 909 C.E. In spite of the great historical role played by the provinces of Tripoli and Barca as a nexus in the region during All Islamic Eras generally and during the Fatimid Era particularly, they did not receive enough attention and historical documentation by Muslim historians and others. Accordingly, this study aimed at discussing and uncovering important aspects of the history of the two provinces during the rule of the Fatimid state. And by using A historical analytical method, which is sometimes based on description, comparison and critical review, The study succeeded to understanding the political situation of the two provinces during the Fatimid Caliphate and the economic life of their population at that time, with a description of the most important aspects of their social life and the foundations of their society, customs and local heritage. It also found that the people of the two provinces were forced to live under the rule of the Fatimids after the failure of several revolutions against them. However, the people then assimilated with the new rule, and worked under the Fatimids for the prosperity of their economic life in various activities, which in turn had a significant impact on their social life that colored by a Fatimids style. The study recommends after completion of it to the importance of furthering the research and uncovering the other aspects of the history of the two provinces such as the cultural and religious lives, Architectural effects and other aspects that accumulatively illustrate a comprehensive picture of the lives of the people of Tripoli of-the-West and Barca during the Fatimid Era.